Improving Students' Writing Achievement Through Describing Picture Technique At SMPN 14 Bengkulu Selatan - Syamsul Rizal; Olvi Satirah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
The Researcher aims for increasing students’ writing achievements through describing picture technique (a classroom action research at the eight grade students of SMPN 14 Bengkulu Selatan in academic year 2013/2014). Because there was the students could not write good paragraph especially in descriptive paragraph and also was not appropriate technique to teach writing. So describing picture technique was effective to improve the students’ writing achievement. The researcher was classroom action research that consists of three steps there were pre-assessment and three cycles. Each cycle was given the implementation of action on teaching materials about describing picture. There were people, place, animals and the last cycle was given reflection and evaluation. This research took subject in the class VIII A of SMPN 14 Bengkulu Selatan. They were consist of 27 test, document, observation, using picture in writing processes. The data in this result of this research was collected by using test and the instrument was used pictures. The result of the research showed that the eight grade students of SMPN 14 Bengkulu Selatan could write good paragraph, especially used of organization, vocabulary, language use and mechanics to write good paragraph. In pre test with average 44. 25 % was very poor, but after giving the action in each cycle the result of the students could write good paragraph and was improved with the last cycle got 72.70% was good. This research indicated that the used describing picture techniques could improve students’ writing achievement at the eight grade students of SMPN 14 Bengkulu Selatan year 2013/2014.